Zatanna and the house of secrets : a graphic novel - Cody, Matthew (DC Comics, 2020)
After standing up to a bully at school, Zatanna rushes home to the House of Secrets to tell her professional magician father. She then discovers her father is missing amid the home's magic, puzzles, and storybook creatures. Now it's up to Zatanna to rescue him.